PELAKSANAAN PEMBERDAYAAN PEREMPUAN DESA AIR TERJUN KECAMATAN BANDAR PETALANGAN KABUPATEN PELALAWAN TAHUN 2017-2019 - Mahabah, Mohammad Arif Nur; Marta, Auradian (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Every year the Air Terjun Village Government continues to strive to develop the potential of village women so that they can develop and make village women independent by creating village women's empowerment programs. Empowerment of Women in Air Terjun Village is quite important to be held, which is a majority of oil palm plantation areas, makes the livelihoods of many people relying on plantation products. The situation is getting more difficult when women are helpless and make no competitiveness in an effort to improve the economy of the people of Air Terjun Village. This study aims to determine to what extent the level of effectiveness of women's empowerment programs in the Air Terjun Village in an effort to increase the independence of women in the Air Terjun village. The approach used in this research is a qualitative approach with descriptive research type. The location of this research was carried out in the Air Terjun Village, Bandar Petalangan District, Pelalawan Regency, with data collection techniques carried out by interviews and documentation.The results of this research are that firstly, the implementation of the women's empowerment program in the Air Terjun Village has been going well, but there are still some obstacles in it, such as the embroidery empowerment program that cannot use all the facilities in the form of the embroidery machine provided because it was damaged while the program was running. Second, the level of effectiveness of the women's empowerment program in the Air Terjun Village in increasing the independence of village women is still ineffective, this can be seen from the lack of development of the participants in the empowerment program after participating in these programs. Keywords: Effectiveness Program, Women Empowerment, Village Government